Sosialisasi Strategi Peningkatan Pemasaran Digital Bagi UMKM - Rahmat Riwayat Abadi; Burhanuddin; Nurul Fadilah Aswar; Annisa Paramaswary Aslam; Ridfan Rifadly Abadi (Sakura Digital Nusantara, 2024)
Local governments are trying to increase MSME’s income by encouraging economic growth through digital marketing. The existence of MSME’s plays a vital role in society because MSME’s greatly influence efforts to increase revenue for the community. The rapid flow of globalization has made technological developments digital, making business actors follow digital trends in response to the changing era. Many people have switched from conventional marketing to digital marketing. This situation emphasizes that business actors must optimize their marketing strategies and productivity by switching to digital marketing. Even amid many new businesses emerging, their companies can survive and grow by adopting digital marketing strategies. Based on these conditions, digital marketing training and development efforts need to be made to market unique and modern products so that they can generate more sales and be widely known to the public. The initial step taken by the community service team was to socialize the community regarding the training and development of digital marketing and strategies. Through the socialization of digital marketing, it is hoped to increase the insight of MSME’s actors about digital marketing strategies and the tools they can use.